Tradisi Ziarah Talang Pada Hari Raya Idul Fitri Di Desa Santapan Kecamatan Kandis Kabupaten Ogan Ilir - Nisa Andriani; Endang Rochmiatun; Otoman Otoman (Tanjak: Sejarah dan Peradaban Islam, 2021)
The research method chosen by the researcher is qualitative research. The results showed that the history of the Talang Pilgrimage in its history was first carried out in 1943. It was started by the family of Hj. Habibun who donated land to his children and grandchildren. This waqf land is used by the community, used as a burial area. Over time, a pilgrimage tradition was formed after Eid. The custom made by the community when attending the Talang pilgrimage is to read greetings before entering the cemetery area, cleaning the burial grounds. clearing the grass that interferes with the road, the goal is so that people can freely pass. This culture is done while eating the available food and drink. In general, the customs or traditions that are carried out by the community when attending the Talang pilgrimage include: first, entering the burial ground. Second, cleaning the cemetery, and third, reading Yasin's letters or praying. Fourth, in this process, the community uses dishes such as throwing flowers and watering 3 times. After doing him and finally getting in touch with relatives who are at the cemetery, the goal is to stay in touch, both to the living and the dead. The benefits of the Talang Pilgrimage and spiritual attachment in the Talang pilgrimage tradition. This tradition is held to always connect with ancestral spirits. It is also intended as an effort to remember and remember death.